PERAN KEPALA SEKOLAH DAN GURU DALAM MENINGKATKAN MUTU PENDIDIKAN PADA ERA MERDEKA BELAJAR UNTUK MENDUKUNG VISI INDONESIA 2045 (STUDI BERBASIS DATA RAPOR PENDIDIKAN) - Vita Meitria; Anam Sutopo; Sofyan Anif (STKIP Subang, 2026)
The transformation of education through the Merdeka Belajar policy requires optimizing the roles of school principals and teachers in improving data-based education quality. This study aims to analyze the roles of principals and teachers in maximizing education quality through the use of education report data in the Merdeka Belajar era to support the vision of Indonesia 2045. The method used is a quantitative descriptive approach with data sources derived from education report data for 2024 and 2025 at an elementary school. Data collection was conducted through documentation, while data analysis was carried out by comparing literacy and numeracy achievements between years. The results show a significant decline in literacy and numeracy achievements, indicated by a decrease in the percentage of students achieving minimum competency and the absence of students in the high-performance category. The discussion reveals that this condition is caused by suboptimal implementation of the Merdeka Curriculum and weak utilization of data in learning planning. The conclusion emphasizes that strengthening the roles of principals and teachers in data-based learning is essential to improve education quality sustainably.